Principal Strategy in Developing Teacher Professional Competence to Improve Quality of Education - Hajon, Aloysia Jawa; Aslamiah, Aslamiah; Sulaiman, Sulaiman (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine and describe in depth the professional development strategy of teachers at Santa Maria and Santa Angela Junor High School with a focus on the discussion of planning, implementation and evaluation of strategies and obstacles faced in developing professional competence of teachers. This study uses a qualitative descriptive approach. Data collection was carried out using interview, observation and documentation. Data analysis techniques used data reduction, data presentation and drawing conclusions. The results of the study indicate that: (1) The Professional Competence Development Strategy of teachers are divided into 3 stages: planning, implementation and supervision, and evaluation; (2) Obstacles faced in developing professional competence of teachers include: Implementation sometimes clashes with teacher activity schedules or with activities at school; The principal's feeling of discomfort in supervising senior teachers; Always using the same trainer with methods that are less interesting, boring and difficult to understand; Limited time for interviews with individual coaching by the Foundation; Lack of awareness and motivation to participate in training and coaching.